Sauer's manual of skin diseases - Hall, Brian J. (Brian John), 1981-; Hall, John C., 1947- (Wolters Kluwer Health, 2017)
Provides full-color photographs, notes to highlight key concepts, and step-by-step instructions for treatment of common skin conditions. The format consists of two distinct parts: the first part covers the diagnosis and management of the most commonly seen skin diseases. The second part is a comprehensive dictionary-index to the entire field of dermatology, including rare diseases and unusual dermatologic terms. --From publisher description.